PENGARUH KARAKTERISTIK AUDITOR TERHADAP PENGHINDARAN PAJAK (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Pada BEI Tahun 2018-2022) - Manullang, Deandra Winona Arista; Hadiprajitno, Paulus Theodorus Basuki (Diponegoro Journal of Accounting, 2024)
Companies do tax avoidance in order to minimize the tax burden that must be paid and increase company profits. Tax avoidance can be seen by using the Effective Tax Rate formula and can be seen in the financial statements. The reliability of financial statements cannot be separated from the role of auditors who conduct in-depth examinations. This study aims to analyze the effect of various auditor characteristics such as audit quality, audit tenure, audit fees, and auditor specialization on tax avoidance in manufacturing companies in Indonesia. The population used in this study are manufacturing companies in Indonesia listed on the IDX in 2018-2022 using purposive sampling method to determine the sample. The total number of samples in this study were 140 samples.  The results in this study indicate that audit quality has a significant negative effect on tax avoidance. Audit tenure, audit fees, and auditor industry specialization have a significant positive effect on tax avoidance. The limitations of this study are that there are other factors that influence tax avoidance that are not examined in this study and there are still many companies that do not include sequential audit fees during 2018-2022.